Karelian Seaside in a Linguistic Context - I. A. Kurshunova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The current state of the study of Russian dialects in Karelian Seaside is analyzed, the territory of the studied region, which coincides with the boundaries of the dialectal division of the Russian language in 1915 is indicated. It is shown that the exclusion of Karelian Seaside from the dialectal division of 1965, which was an indirect reason for the lack of proper research attention to this region is unjustified. An overview of linguistic works devoted to the study of various language levels (phonetic, grammatical, lexical) is presented. The review of dictionaries, including the vocabulary of Russian dialects of the Karelian Seaside, is carried out. The prospects and objectives of the study are determined. In particular, future research is associated with comparative work on the study of the preservation / change of linguistic phenomena at each level, including the lexical one, which is the most stable in its main core. It is primarily due to extralinguistic reasons. Particular attention is paid to the use of digital technologies when creating a textual database, tested on the materials of the Karelian Seaside. It is noted that the electronic resource will make it possible to constantly introduce new data into scientific circulation, connecting them to various aspects of research, both linguistic and broader humanitarian.